“Black flowers”, vozes pela liberdade - Paixão, Marcelo (Afro-Ásia, 2023)
Resenha de: Raussert, Wilfried; e Steinitz, Matti (Orgs.). Black Power in Hemispheric Perspective: Movements and Cultures of Resistance in the Black Americas. Trier: Wissenschaftlicher Verlag Trier; Nova Orleans: University of New Orleans Press, 2022. 280 p.